2013
DOI: 10.1186/0778-7367-71-20
|View full text |Cite
|
Sign up to set email alerts
|

Do mass media campaigns improve physical activity? a systematic review and meta-analysis

Abstract: BackgroundMass media campaigns are frequently used to influence the health behaviors of various populations. There are currently no quantitative meta-analyses of the effect of mass media campaigns on physical activity in adults.MethodsWe searched six electronic databases from their inception to August 2012 and selected prospective studies that evaluated the effect of mass media campaigns on physical activity in adults. We excluded studies that did not have a proper control group or did not report the uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 28 publications
(43 reference statements)
0
53
0
2
Order By: Relevance
“…37 For example, a meta-analysis of 9 studies promoting walking reported that mass media campaigns increased the likelihood of meeting sufficient walking goals (defined as brisk walking for 150 minutes a week) by 53% (pooled relative risk 1.53; 95% CI,1.25-1.87). 38 Because many women in our study reported that it was difficult to make too many changes from their prepregnancy patterns of eating and exercise, these campaigns ideally should begin before women become pregnant.…”
Section: Discussionmentioning
confidence: 97%
“…37 For example, a meta-analysis of 9 studies promoting walking reported that mass media campaigns increased the likelihood of meeting sufficient walking goals (defined as brisk walking for 150 minutes a week) by 53% (pooled relative risk 1.53; 95% CI,1.25-1.87). 38 Because many women in our study reported that it was difficult to make too many changes from their prepregnancy patterns of eating and exercise, these campaigns ideally should begin before women become pregnant.…”
Section: Discussionmentioning
confidence: 97%
“…However, 4 in 5 U.S. adults do not meet recommended levels of physical activity guidelines [3]. Various programs such as provision of economic incentives [4], mass media campaigns [5], point-of-decision prompts [6], neighborhood built environment remodeling [7], social network interventions [8], etc., have been employed to promote active living. However, existing programs addressing sedentary behavior and physical inactivity have only limited success in facilitating long-term behavior modification and maintenance [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Although evaluations from such mass media campaigns have reported significant increases in physical activity levels (Abioye, Hajifathalian, & Danaei, 2013), it is still unclear what types of message strategies are most effective in increasing physical activity, especially for highrisk populations.…”
Section: Promoting Physical Activity With Group Picturesmentioning
confidence: 99%